Mechanisms of Renin Secretion during Hemorrhage in the Dog - Henrich, William L. (1979)
The importance of renal perfusion pressure (RPP), the sympathetic beta adrenergic nervous system and renal prostaglandins (PG) on renin release during a uniform 15-17% reduction in blood pressure by hemorrhage (HH) was studied systematically in anesthetized dogs. All groups of animals had similar decrements in systemic and renal hemodynamics with HH. In control dogs (n = 7), both plasma renin activity (PRA, 4.1-9.0 ng angiotensin I/ml per h, P < 0.05) and renin secretory rate (RSR, 26-228 ng/ml per h·min, P < 0.005) increased significantly with HH. This increase in renin release during HH was not abolished by any single maneuver alone including beta adrenergic blockade with d,l-propranolol (n = 6), renal PG inhibition with indomethacin (n = 7), or control of RPP (n = 6). However, when beta adrenergic blockade was combined with control of RPP (n = 7) during HH, neither PRA (1.9-2.7 ng/ml per h, NS) nor RSR (16-53 ng/ml per h·min, NS) increased significantly. Similarly, a combination of beta adrenergic blockade and PG inhibition (n = 6) also abolished the increase in PRA (1.5-1.4 ng/ml per h, NS) and RSR (14-55 ng/ml per h·min, NS) during HH despite significant decreases in sodium excretion. Finally, a combination of PG inhibition and RPP control was associated with significant increases in PRA and RSR during HH. These results support a multifactorial mechanism in renin release during HH and implicate both the beta adrenergic receptors, renal baroreceptors, and possibly the macula densa as constituting the primary pathways of renin release during HH of this magnitude. Because either constant RPP or PG inhibition blunted renin release during HH in the setting of beta adrenergic blockade, the present results strongly suggest that the renal baroreceptor, and probably the macula densa mechanism are PG mediated.